Characterization and in vitro degradation studies of synthesized polylactide (PLA) - Gaurava S.; Ankita M.; Pradeep S. (My University, 2025)
Biodegradable polymers represent a useful class of biomaterials. In this study, a biodegradable polymer, poly (L-Lactide) (PLA), synthesized by the optimized process1 was characterized for its suitability for biomedical applications. A pre-polymer was synthesized by carrying out a controlled condensation reaction, then post-polymerized by ring opening the pre-polymer at 165°C. In this paper, the synthesized polymer was characterized by FT-IR, 1H NMR, 13C NMR, Viscometry, GPC and DSC. Measurements on the mechanical properties of PLA testified that the synthesized polymers are polymers degradation of the polymer beads in a bffu er of pH with low hardness and big elongation and hydrolytic 7.4 at 37 °C showed that PLA had excellent degradability (all the beads show the weight losses more than 60% after 2 weeks incubation). Degradation study shows that hydrolytic breakdown of PLA polymers is strongly influenced by the presence of BSA in the degradation media. The material is expected to be useful for controlled drug delivery and other biomedical applications.